2018
DOI: 10.1021/acsnano.8b04713
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Noise in Graphene Tunnel Junctions

Abstract: Graphene tunnel junctions are a promising experimental platform for single molecule electronics and biosensing. Ultimately their noise properties will play a critical role in developing these applications. Here we report a study of electrical noise in graphene tunnel junctions fabricated through feedback-controlled electroburning. We observe random telegraph signals characterized by a Lorentzian noise spectrum at cryogenic temperatures (77 K) and a 1/ f noise spectrum at room temperature. To gain insight into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 90 publications
0
26
0
Order By: Relevance
“…Such a robust analysis is useful, for example, when reporting on molecular switches. Switching may have several underlying mechanisms, some of which are not related to the internal structure of the molecule but could instead be attributable to mechanical instability of the junctions or changes in the electronic coupling between the molecule and the electrodes 131 , changes in the electrostatic environment (including the substrate) 132 or the presence of ions that are needed to stabilize the molecule 133 .…”
Section: [H1] Conclusion and Outlookmentioning
confidence: 99%
“…Such a robust analysis is useful, for example, when reporting on molecular switches. Switching may have several underlying mechanisms, some of which are not related to the internal structure of the molecule but could instead be attributable to mechanical instability of the junctions or changes in the electronic coupling between the molecule and the electrodes 131 , changes in the electrostatic environment (including the substrate) 132 or the presence of ions that are needed to stabilize the molecule 133 .…”
Section: [H1] Conclusion and Outlookmentioning
confidence: 99%
“…Moreover, nanometer scale conductors are known to be especially sensitive to internal or environmental fluctuations. [20][21][22] For this reason, the thorough characterization and understanding of electronic noise in atomic scale metallic filaments represent a fundamental prerequisite toward their practical applications in neuromorphic computing.…”
mentioning
confidence: 99%
“…This issue serve as another challenge in this field as some studies on the noise characteristics of graphene structures have been reported at cryogenic temperatures and under high vacuum. 68,69…”
Section: Discussionmentioning
confidence: 99%